Plasma Cystatin B Association With Abdominal Aortic Aneurysms and Need for Later Surgical Repair: A Sub-study of the VIVA Trial. (December 2018) - Wang, Yunzhe; Liu, Cong-Lin; Lindholt, Jes S.; Shi, Guo-Ping; Zhang, Jinying
Abstract : Objective/background: The development of an abdominal aortic aneurysm (AAA) involves extensive extracellular matrix remodelling, leading to aortic wall weakening. This process is mediated by proteases, including cysteinyl cathepsins. Cystatins are their endogenous inhibitors. This study tested whether plasma cystatin B levels in patients with AAA differed from those of healthy controls. Methods: Plasma samples from patients with AAA and age matched controls were selected from the Viborg Vascular (VIVA) screening trial for AAA. Enzyme linked immunosorbent assay determined plasma cystatin B. T-test, logistic regression, Pearson's correlation and Cox regression tested whether plasma cystatin B correlates with AAA size and growth rate, or serves as a marker for AAA. Results: Plasma cystatin B levels were significantly higher in patients with AAA than in controls ( p < 0.001). Logistic regression analysis showed that cystatin B tertile at baseline was associated with the presence of AAA before (odds ratio [OR] 1.656; p < 0.001) and after adjustment for peripheral arterial disease (PAD), chronic obstructive pulmonary disease (COPD), and previous ischaemic events (OR 1.526; p < 0.001). A t -test showed a significant association between cystatin B and PAD at screening, hospital diagnosis of COPD, previous atherosclerotic events, and use of low dose aspirin. Pearson's correlation test showed positive and significant associations between cystatin B and AAA size ( r = 0.15; p < 0.001). Cox regression test showed that plasma cystatin B tertile at baseline was associated with later AAA surgical repair before (hazard ratio [HR] 1.387; p < 0.001) and after adjustment for PAD, COPD, previous ischaemic event, and maximum infrarenal aortic diameter (HR 1.523; p < 0.001). Conclusion: In contrast to prior studies that showed that cystatin C is negatively associated with AAA development, this study demonstrated a positive association between cystatin B and AAA size and associations between cystatin B tertile at baseline and AAA presence and need for later surgical repair. It is possible that these two cystatins inhibit cathepsin activity and participate in AAA with different mechanisms.